ANALISIS PENGARUH MODAL SOSIAL TERHADAP KINERJA USAHATANI PADI SAWAH DI KELURAHAN PUNGGALUKU KECAMATAN LAEYA KABUPATEN KONAWE SELATAN - Alisa Alisa; Yani Taufik; Salahuddin Salahuddin (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The objective of this study is to examine the influence of social capital on the performance of rice farming in Punggaluku Village, Laeya District, South Konawe Regency. The research population consists of all rice farmers in Punggaluku Village, with a total of 140 individuals. The determination of the sample size for this study was made using the Slovin formula, with a margin of error set at 10%. Therefore, the sample size was determined to be 58 respondents. The sampling method employed was a simple random sampling technique. The data presented herein was collected through a variety of research techniques, including in-depth interviews, meticulous documentation analysis, a thorough review of existing literature, and the administration of surveys. The research variables consisted of exogenous variables (social capital) and endogenous variables (farming performance). The collected data underwent a dual analytical process, comprising a preliminary descriptive statistical evaluation, followed by an inferential statistical examination. The results of the study indicate that social capital, particularly social norms and networks, is well established among the community involved in rice farming. Most farmers actively practice social norms and networks, such as attending farmer group meetings and complying with cultivation rules, as well as building strong networks through easy access to information, both from fellow farmers and external institutions. Meanwhile, the aspect of trust is considered adequate, indicating room for improvement in mutual trust among group members and extension workers. The performance of rice farming, as measured by the quantity and quality of farmers' work, has been carried out well, while timeliness remains in the adequate category. Social capital has a positive and significant impact on farming performance, as indicated by the simple linear regression coefficient (β = 1.049). Social capital, as a non-material resource comprising norms, networks, and trust, has a tangible impact on the productivity and effectiveness of farming.